2013
DOI: 10.1021/ac400590c
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Device for Efficient Airborne Bacteria Capture and Enrichment

Abstract: Highly efficient capture and enrichment is always the key for rapid analysis of airborne pathogens. Herein we report a simple microfluidic device which is capable of fast and efficient airborne bacteria capture and enrichment. The device was validated with Escherichia coli (E. coli) and Mycobacterium smegmatis. The results showed that the efficiency can reach close to 100% in 9 min. Compared with the traditional sediment method, there is also great improvement with capture limit. In addition, various flow rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 57 publications
2
94
0
Order By: Relevance
“…Jing et al . 118 developed a PMMA/PDMS hybrid microfluidic device for efficient airborne bacteria capture and enrichment. The device had two PDMS plates sandwiched by two plates of PMMA using four screws for structural support.…”
Section: Biomarker Detection Methods For Disease Diagnosis Using Mmentioning
confidence: 99%
“…Jing et al . 118 developed a PMMA/PDMS hybrid microfluidic device for efficient airborne bacteria capture and enrichment. The device had two PDMS plates sandwiched by two plates of PMMA using four screws for structural support.…”
Section: Biomarker Detection Methods For Disease Diagnosis Using Mmentioning
confidence: 99%
“…Characteristic antigen (protein)immune analyses as well as nucleic acid ana lysis by hybridization or PCR were successfully performed in microfluidic chips. Recently, the capture and enrichment of airborne bacteria by microfluidic chips was also reported [15]. By breaking the laminar flow to twisted air flow inside the microfluidic chip, increasing the contact opportunity between the channel wall and the bacteria in the airflow, the microfluidic chip can collect hundreds of bacteria within a couple of microliters of aqueous media, high enough concentration for direct immunoana lysis or nucleic acid ana lysis.…”
Section: Microfluidics For Airborne Pathogen Ana Lysis and Remaining Tementioning
confidence: 99%
“…In designing a system, concentration rate should be optimized by increasing the air flow rate and collection efficiency, or decreasing the volume of capture liquid preferably to microfluidic volumes, because this improves the aerosol detection sensitivity. Past studies reconciling microfluidics with aerosol collection (by deposition of aerosol in channels/half-channels) have reported concentration rates of 10 4 -10 6 min ¡1 , and have delineated the limitations with these approaches (Han and Mainelis 2008;Han et al 2010Han et al , 2011Jing et al 2013Jing et al , 2014Pardon et al 2015;Han et al 2015a,b;Foat et al 2016;Ma et al 2016). These studies have shown successes, but require further work in integration with assay platforms, clearly demonstrating end-to-end bioaerosol collection and identification, estimating limits of detection, and detailed field testing.…”
Section: Introductionmentioning
confidence: 99%